Character Education Based on the Stories of the Prophets in Islamic Early Childhood Education: Analysis of Pedagogical Strategies and Implementation Factors - Kurniati, Nia; Darajaatul, Nelud (Journal of Social Science Studies, 2024)
Character education in early childhood is a critical foundation for personality development. In Islamic early childhood education, the stories of prophets and messengers are believed to be authentic sources of moral values. This academic paper, based on a literature review, aims to analyses the application of character education based on the stories of prophets in Islamic early childhood education, focusing on the conceptualization of stories as a pedagogical medium, effective delivery strategies, and factors that support and hinder its implementation. The study was conducted using a qualitative approach with a thematic synthesis method of relevant literature. The results show that the stories of the prophets serve as a source of values and a powerful narrative medium for building children’s Islamic identity and moral development. Effective pedagogical strategies must be interactive and child-centered, such as interactive storytelling, role-playing, and thematic approaches. Sustainable implementation is greatly influenced by factors such as teacher capacity, institutional leadership, parental support, and the availability of resources and evaluation systems. This paper concludes that the success of this approach requires a mature integration of the richness of Islamic heritage with the principles of modern early childhood pedagogy, supported by systematic institutional management and collaboration with all stakeholders.